2020
DOI: 10.1016/j.pecs.2019.100801
|View full text |Cite
|
Sign up to set email alerts
|

Role of firebrand combustion in large outdoor fire spread

Abstract: Large outdoor fires are an increasing danger to the built environment. Wildfires that spread into communities, labeled as Wildland-Urban Interface (WUI) fires, are an example of large outdoor fires. Other examples of large outdoor fires are urban fires including those that may occur after earthquakes as well as in informal settlements. When vegetation and structures burn in large outdoor fires, pieces of burning material, known as firebrands, are generated, become lofted, and may be carried by the wind. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 91 publications
2
72
0
Order By: Relevance
“…Previous investigations have shown that firebrands are a major cause of fire spread during WUI fires, igniting structures and secondary fires far away from the main fire front (Mell et al, 2010), thus complicating suppression efforts. While early works by Cohen (2008) and numerous investigations by Maranghides and Mell (2011), Maranghides et al (2013), Maranghides et al (2015), and Maranghides and McNamara (2016) have shown that firebrands are a major source of structural losses, our understanding of the physical mechanisms by which firebrands generate, loft, and eventually ignite structures is still in its early stages (Caton et al, 2016;Manzello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that firebrands are a major cause of fire spread during WUI fires, igniting structures and secondary fires far away from the main fire front (Mell et al, 2010), thus complicating suppression efforts. While early works by Cohen (2008) and numerous investigations by Maranghides and Mell (2011), Maranghides et al (2013), Maranghides et al (2015), and Maranghides and McNamara (2016) have shown that firebrands are a major source of structural losses, our understanding of the physical mechanisms by which firebrands generate, loft, and eventually ignite structures is still in its early stages (Caton et al, 2016;Manzello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is partly attributed to ease of ignition of common roofing materials, the extensive surface area exposed to an ember shower, and capability of subsequent ember production from burning roofs [8]. Vulnerabilities of buildings to wildfire exposures have been recognized and reported by Manzello et al [9]. It is difficult to control wildfires directly; however, it is certainly feasible to reduce structural fires by fire hardening the structures located in the WUI communities.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of exposurewhere a combustible solid substrate is in direct contact with a smoldering ignition sourceis not included in the existing test methods (except for roofing and decking materials). This is notable because burned structures within the WUI communities have been lost long after they might be considered safe from direct flaming exposures [3,6,8,9,[14][15][16]. Accumulation of embers in a corner or crevice configurations is very likely, and the probability of ignitions in such configurations is very high [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…1. Firebrands are pro-duced and lead to enhanced fire spread processes [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Often referred to as spotting processes, firebrands are liberated from the combustion of various fuel types, such as trees, shrubs, houses, and then induce ignition of fuel sources away from the initial fire source.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of short distance spot fires (distance up to 500 m to 750 m [28]), a potentially important aspect of the physics of ignition induced by firebrand are the coupled influence of firebrand showers and radiant heat. Many past investigations have focused on singular effects on fire spread [11,[23][24][25][26][27], and little is known about coupled effects.…”
Section: Introductionmentioning
confidence: 99%